Level of Knowledge, Attitude About Reproductive Health and Gender with Teenager Sexual Behaviour at SMAN 4 Kendari - Sriyana Herman; Amiruddin Amiruddin; Muhammad Sirih; Ardina Ardina; Rusli Rusli (Universitas Airlangga, 2023)
To know the correlation between the level of knowledge about reproductive health, attitude about reproductive health and gender with the teenager sexual behavior at SMAN 4 Kendari. The research population is class X and XI SMAN 4 Kendari student which amount 827 people. The sample retrieval technique is proportional stratified random sampling thus gained as much as 270 respondents. Data collection technique are done with an analytic survey through a cross sectional approach. The data analysis technique’s using descriptive and inferential statistics. The results: Showed that the men as much as 117 respondents (43,33%), women 152 respondents (56,67%), high level of knowledge as much as 160 respondents (59,26%), level of intermediate knowledge 73 respondents (27,04%), low knowledge level 37 respondents (13,7%), a good attitude as much as 76 respondents (28,15%), a medium attitude 147 respondents (54,44%), a deficient attitude 47 respondents (17,41%), sexual behavior is risk as much as 244 respondents (90,37%), and sexual behavior is not risk 26 respondents (9,63%). The level of knowledge is unrelated to the teenager sexual behavior (p > 0,05), attitude is related to the teenager sexual behavior (p < 0,05), and gender is related to the teenager sexual behavior (p < 0,05).